Polychaetous annelids of the Polynoidae from the northeastern Pacific, with a description of a new species - Pettibone, M. H. (American Museum Novitates, 1949)
[introduction] In connection with a study of the scaled polychaetes of San Juan Archipelago and adjacent regions, a check was made on the types of the species Gattyana imbricata Treadwell (Treadwell, 1926), the specimens of which were kindly lent to me by the American Museum of Natural History. The parts of nine speci- mens labeled by Treadwell as G. imbrtcata Treadwell proved to involve six species-five known and one unknown. The specimen of the latter species (see below, under new species) was not used in the original description of G. imbricata by Treadwell. He used three specimens which proved to be G. cirrosa (Pallas) and Evar- nella triannulata (Moore), thus making Gattyana imbricata Tread- well an invalid species. The polychaetes were collected by Capt. R. A. Bartlett in Alaska in the general region of Bering Strait in 1924, under the auspices of the National Geographic Society. The species represented and the localities where they were ob- tained are as follows.
Kristian Fauchald's Polychaeta DB